Lived Experiences of School Heads During Post-Pandemic: Building Resilience and Navigating Schools to Recovery Amidst Disruptive Times - Jermaine D. Alonzo; Alberto D. Yazon; Karen A. Manaig; Lerma P. Buenvinida; Marcial M. Bandoy (Research Synergy Foundation, 2024)
Crisis management practices among school leaders are critical for effective emergency response and resilience. Crisis management studies are essential because unanticipated crises, such as health concerns and calamities, disrupt the learning process. This phenomenological research explores the lived experiences of school heads during the post-pandemic period when they built resilience and navigated their schools back to recovery. Adapting to changing circumstances, finding effective ways to bridge learning gaps and promoting staff and learner well-being are the major challenges facing school heads after pandemic. Real-life situations are further explored through this research to aid in crisis management. This study is crucial because it aids organizations in their effective planning, rapid response, and recovery from unexpected crises. Eight school heads from the Philippines were selected as participants. The researcher utilized a validated questionnaire to gather data on various school management strategies before and after the pandemic. The post-pandemic posed challenges, needs, and opportunities due to protocols, settings, and requirements while incorporating resilience strategies and implementing proactive school recovery approaches. The ANCHOR model was developed as a crisis management framework based on the findings and observations. This process consists of five stages: acclimatization, necessity appraisal, counter-response and handling, opportune resilience strategies application, and recovery and restructuring. It can be applied by organizations to manage crises and recover, emphasizing crisis management skills to improve organizational performance. The model can aid school heads in making informed decisions and navigate institutions to recovery. Finally, this research encapsulates that crisis management skills are essential to organizational performance, particularly in academic institutions.